PHYSICAL TRAINING IN MILITARY-PATRIOTIC TRAINING OF RESERVE OFFICERS IN THE SYSTEM OF HIGHER EDUCATION IN UNIVERSITIES - Aleksandr D. Kudrya; Elena U. Ayrapetova (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the importance of physical culture as an integral part of military-patriotic education, the preparation of reserve officers in the higher education system in universities, which implement a training program for reserve officers.